2008
DOI: 10.1037/0021-9010.93.2.346
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transformational and change leadership on employees' commitment to a change: A multilevel study.

Abstract: The effects of transformational leadership on the outcomes of specific change initiatives are not well understood. Conversely, organizational change studies have examined leader behaviors during specific change implementations yet have failed to link these to broader leadership theories. In this study, the authors investigate the relationship between transformational and change leadership and followers' commitment to a particular change initiative as a function of the personal impact of the changes. Transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
576
4
20

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 536 publications
(662 citation statements)
references
References 50 publications
22
576
4
20
Order By: Relevance
“…Using multiple regressions and hierarchical regression, we found that transformational leadership were positively significant related to employee affective commitment to change in the same line with other findings (Herold, Fedor, Caldwell, & Liu, 2008) which found that transformational leadership were positively related to employee commitment to change.…”
Section: Discussionsupporting
confidence: 79%
“…Using multiple regressions and hierarchical regression, we found that transformational leadership were positively significant related to employee affective commitment to change in the same line with other findings (Herold, Fedor, Caldwell, & Liu, 2008) which found that transformational leadership were positively related to employee commitment to change.…”
Section: Discussionsupporting
confidence: 79%
“…A transformational leadership style can impact others' commitment to change and their level of effectiveness. Herold, Fedor, and Cladwell (2008) found that under conditions of high personal job impact transformational leadership was positively associated with change commitment. Lastly, House (1976) brought to transformational leadership the idea of charisma.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Herold, Fedor, Caldwell, & Liu, 2008). In part, this stems from our failure to clearly distinguish leadership and management as distinct phenomena.…”
Section: Myth 2: Leadership Is Enoughmentioning
confidence: 99%